Michael Symon's 5 in 5 for every season : 165 quick dinners, sides, holiday dishes, and more - Symon, Michael, 1969-; Trattner, Douglas (Clarkson Potter/Publishers, 2015)
"Ridiculously easy from-scratch recipes to get you in and out of the kitchen in a flash every day of the week--now with sides and holiday dishes, too. The follow-up to the bestselling Michael Symon's 5 in 5, this new book delivers 165 quick, fresh recipes organized by season with an entire section devoted to making the holidays simpler than ever. Each chapter features inspired main courses as well as recipes for sides and 5 fun ways to celebrate the season, including no-bake summer fruit desserts and spiked drinks to warm up witn in winter,"--page [4] of cover.